2004
DOI: 10.1124/mol.104.005314
|View full text |Cite
|
Sign up to set email alerts
|

Kv2.1 Channel Activation and Inactivation Is Influenced by Physical Interactions of Both Syntaxin 1A and the Syntaxin 1A/SolubleN-Ethylmaleimide-Sensitive Factor-25 (t-SNARE) Complex with the C Terminus of the Channel

Abstract: Kv2.1, the prevalent delayed-rectifier K ϩ channel in neuroendocrine and endocrine cells, was suggested previously by our group to be modulated in islet ␤-cells by syntaxin 1A (Syx) and soluble N-ethylmaleimide-sensitive factor attachment protein-25 . We also demonstrated physical interactions in neuroendocrine cells between Kv2.1, Syx, and SNAP-25, characterized their effects on Kv2.1 activation and inactivation in Xenopus laevis oocytes, and suggested that they pertain to the assembly/disassembly of the Syx/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
(48 reference statements)
3
31
1
Order By: Relevance
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…35 S]Met/Cys-labeled oocytes were subjected to immunoprecipitation as described previously (Michaelevski et al, 2003;Tsuk et al, 2005). Oocytes were injected with 0.75 ng/oocyte syntaxin, 5 ng/oocyte Kv2.1, or 15 ng/oocyte Kv2.1⌬C1a mRNAs, as indicated in Figure 5c.…”
Section: Methodsmentioning
confidence: 99%
“…4a) but not to the C terminus of Kv1.1 (Fili et al, 2001;Michaelevski et al, 2003;Tsuk et al, 2005). Therefore, we examined whether the Kv2.1 syntaxin-binding peptides could be used to compete for the in vivo association of syntaxin with Kv2.1.…”
Section: Kv21-derived Syntaxin-binding Peptides Inhibit the Facilitamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, syntaxin 1A (Syx), a plasma membrane protein component of the exocytotic SNARE complex, shown to interact physically and functionally with different voltage-gated K ϩ channels (Fili et al, 2001;Leung et al, 2003Leung et al, , 2007Michaelevski et al, 2003Michaelevski et al, , 2007Tsuk et al, 2005;Yamakawa et al, 2007;Regev et al, 2009), was suggested to be another blocker of M-channels (Regev et al, 2009). …”
Section: Introductionmentioning
confidence: 99%